Effects of petrographical rock properties to the strength and behavior of rock - Samsuri, Ariffin; Sukirman, Yahya; Pham, Vu Chuong (1999)
This paper presents the study of the relationship between petrographical rock properties to strength and behavior of the rock. The study was conducted on sandstone core sample of Pahang, Malaysia. The petrographical rock properties such as mineralogy, grain size sorting and concentration were studied by thin section and X-Ray diffractometry (XRD) analysis. The strength and behavior of rock such as compressive strength (Co), tensile strength (To), shear strength (So), friction angle (Ã¸), young's modulus (E), poisson's ratio (Ï…)and rock behavior were studied by using Servo Control Hydraulic Testing Machine (SCHTM). The results show that for finer grain size, poorer sorted sand, higher amount of quartz, feldspar, other stable minerals and higher degree of concentration, there will be higher Co, To, So, Ã¸ ,E, Ï… and these rocks behave more elastically.